MEMBACA KEARIFAN LOKAL SUKU SASAK (TEMBANG) PADA SENI PERTUNJUKAN SILANG MEDIA: TANAH DIALEKTIKA “LIVE STREAMING, TEMBANG, DENGKREK” - Renda, Rapi; Qatrunnada, Qatrunnada (Boting Langi: Jurnal Seni Pertunjukan, 2025)
This research aims to re-explore the local wisdom of the Sasak community specifically tembang (traditional chant) as a form of oral cultural heritage that is reinterpreted through a cross-media performance titled Tanah Dialektika: Live Streaming, Tembang, Dengkrek. In this performance, exploration is conducted through the collaboration of traditional expressions (tembang and dengkrek) with digital technology (live streaming), forming a performative space that is not only cross-medium but also cross-temporal. This study employs a qualitative descriptive method to examine how performance art serves not merely as an aesthetic domain, but also as a dialectical medium between local values and the evolution of new media, a practice referred to here as cross media performance. This fusion becomes a creative strategy to sustain traditional values within the contemporary realm while also broadening audience engagement. The resulting creative process places tembang as the narrative core and a convergence point between local expression and technological possibilities. The primary research data is the performance Tanah Dialektika: Live Streaming, Tembang, Dengkrek, a collaborative work involving artists from West Nusa Tenggara, presented during FKSM 2023. Data sources include video recordings uploaded to the Literasi Teater and Seniman Kolaborasi YouTube channels. Field research was conducted at the West Nusa Tenggara Cultural Center. The findings show that cross-media performance can serve as both an artistic and cultural strategy to preserve, respond to, and revitalize local wisdom in the rapidly evolving digital landscape.